Kewenangan Dinas Perhubungan dalam Mewujudkan Tertib Lalu Lintas di Wilayah Kota Administrasi Jakarta Pusat - Al Karim, Habib Musa; Hapsoro, Fakhris Lutfianto (Jurnal Kewarganegaraan, 2022)
AbstrakPersoalan kemacetan di DKI Jakarta, khususnya di Kota Administrasi Jakarta Pusat menyebabkan kelancaran lalu lintas menjadi terganggu. Penelitian ini merumuskan dua permasalahan, yaitu bagaimana kewenangan Dinas Perhubungan Kota Administrasi Jakarta Pusat dalam melakukan penertiban lalu lintas di Kota Adminitsrasi Jakarta Pusat, dan bagaimana efektivitas hukum pelaksanaan kewenangan Dinas Perhubungan Kota Administrasi Jakarta Pusat. Penelitian ini menggunakan metode yuridis normatif dan yuridis empiris. Berdasarkan hasil penelitian, ditemukan bahwa ada dua upaya sebagai kewenangan Dinas Perhubungan kota administrasi Jakarta Pusat dalam mewujudkan tertib lalu lintas di Jakarta Pusat, yaitu upaya persuasif, dan upaya represif. Adapun hambatan dalam mewujudkan tertib lalu lintas melalui penegakan hukum ini adalah kurangnya kesadaran masyarakat terhadap aturan Hukum yang telah ada, perubahan fungsi kawasan/lahan menyebabkan timbulnya tarikan atau bangkitan lalu lintas yang baru, belum memadainya transportasi umum yang dapat dijadikan alter- natif sehingga merubah mindset masyarakat dalam penggunaan kendaraan, dan animo masyarakat terhadap kebutuhan kendaraan pribadi tidak sejalan dengan ketersediaan la- han parkir dan kapasitas jalan di wilayah kota admiistrasi Jakarta Pusat yang setiap tahun cenderung mengalami kenaikan.Kata Kunci: Kewenangan, Efektivitas Hukum, Lalu Lintas, Jakarta PusatÂ AbstractThe problem of congestion in DKI Jakarta, especially in the administrative city of Cen- tral Jakarta, is caused by limited parking spaces. Causing the smooth flow of traffic to be disrupted, resulting in a reduction in the effective width of the road and by itself reducing the capacity of the relevant road space. As a result, it will have an impact on traffic jams to traffic accidents. The preparation of this journal formulates problems regarding the active role carried out by the Central Jakarta City Administration of Transportation for the smooth flow of traffic on the road, motorized vehicles parked on the shoulder/body of the road and the factors that become obstacles in realizing orderly traffic on the road. Central Jakarta area by using normative juridical and empirical juridical research types. From the results of the study was revealed that the Regional Apparatus Work Unit (SKPD) of the Transportation Service Office of Central Jakarta administration in realiz- ing traffic order, namely by persuasive efforts, namely conducting socialization and com- munication and carrying out law enforcement in the form of repressive efforts by provid- ing sanctions for parking violations that are not in accordance with provision. The obsta- cles in realizing traffic order through law enforcement are the lack of public awareness of the existing legal rules, changes in the function of the area/land causing new traffic at- traction or generation, inadequate public transportation that can be used as an alterna- tive so that it changes the mindset community in using vehicles, and public interest in the need for private vehicles is not in line with the availability of parking lots and road ca- pacity in the administrative city area of Central Jakarta which tends to increase every year.Keywords: Law enforcement, traffic order